2018
DOI: 10.1002/hep.29669
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic localization of the cell polarity factor scribble supports liver tumor formation and tumor cell invasiveness

Abstract: Perturbation of hepatocellular polarity due to overexpression and cytoplasmic enrichment of Scrib supports tumor initiation and HCC cell dissemination through specific molecular mechanisms. Biomarker signatures identified in this study can be used for the identification of HCC patients with higher risk for the development of metastasis. (Hepatology 2018;67:1842-1856).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 37 publications
4
55
0
Order By: Relevance
“…We and others have demonstrated the importance of SCRIB and LANO in cancer development . In this study, we identified large protein complexes associated with these two paralogues and carried out for the first‐time a direct comparison of their associated protein complexes.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have demonstrated the importance of SCRIB and LANO in cancer development . In this study, we identified large protein complexes associated with these two paralogues and carried out for the first‐time a direct comparison of their associated protein complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, EMT has been recognized as a prometastatic cellular event that promotes tumor cell invasion and malignant tumor progression [5]. Although recent studies have raised concerns about the actual contribution of EMT to metastasis in lung cancer [6] and pancreatic cancer [7], the experimental results acquired in HCC still support the idea that EMT plays a pivotal role in HCC metastasis [8][9][10][11]. Loss of E-cadherin, a typical marker of epithelial cells, is one of the key features of the EMT process and has been implicated in tumor metastasis [12].…”
Section: Introductionmentioning
confidence: 99%
“…Peritoneum was opened by incision and the remaining uid was collected by Pasteur pipette. After transfection, 1x107 Cells in cultured T75 cell culture ask were collected and incubated with formaldehyde/PBS (1%) for 12 minutes to allow cross-linking of DNA and protein according to a ChIP protocol previously described (13). Protein in the complex was diluted to 1 mg/ml with RIPA buffer and pre-cleared with 30 µl of Dynabeads Protein G (Nanoeast Biotech, Jiangsu, China).…”
Section: Mouse Experiments and Macrophage Isolationmentioning
confidence: 99%